Adenoid cystic carcinoma of the breast - Olszewska, Monika; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2017)
Adenoid cystic carcinoma is an invasive cancer accounting for less than 0.1% of all breast cancers. It most frequently occurs as a single, clearly defined, tender tumour. Mammographic and ultrasound images are non-characteristic and may be misinterpreted as benign change. This cancer shows no expression of ER, PGR, and HER-2 receptors; however, as opposed to triple-negative breast cancers, NST has a mild course and sporadically gives rise to metastases to locoregional lymph nodes and distant metastases. There is no consensus concerning the optimum treatment. The surgeries usually performed are lumpectomy with an open sentinel lymph node biopsy and mastectomy. However, considering the low probability of the presence of metastases in the lymph nodes, doubts arise pertaining to the justification for lymph node resection. Adjuvant radiotherapy is recommended after breast-conserving surgeries, especially with positive margins. The role of chemotherapy has not been well recognised, and hormone therapy is not recommended.